Seed biometry: another functional trait in caatinga - Marcelo da Costa Patrício; Dilma Maria de Brito Melo Trovão (Acta Scientiarum. Biological Sciences, 2020)
Seed biometrics is an excellent tool for understanding environmental filters, species potential and dispersal, successional stages of communities and the dynamics used by seeds to germinate, establish and develop, thus constituting a functional trait of the species. We aim to understand the relationship between aspects of seed biometrics and other phenological traits, in order to infer contributions about functional strategies in Caatinga. Between September 2017 and January 2019, 10 individuals of Cenostigma pyramidale (Tul.) LP Queiroz, Commiphora lepthophloeos (Mart.) JB Gillett, Jatropha mollissima (Pohl.) Baill., Monteverdia rigida (Mart.) Biral. Pseudobombax marginatum (A.ST.-Hil) A. Robyns, Zizyphus joazeiro Mart. were monitored for the selection of three seed collection matrices. From each matrix 100 seeds were collected, which after screening resulted in 35 intact seeds that were used to measure length, width, thickness and volume. Caatinga seeds are generally small, as a result of the environmental stresses of the Brazilian semiarid. The analyzed variables separated three groups in the PCA. We noticed that these groups evidenced the successional stages in the Caatinga. One group included M. rigida and P. marginatum, which are late secondary. C. pyramidale and C. lepthophloeos formed another group coincident with intermediate successional stages. J. mollissima and Z. joazeiro formed a group of pioneer species in anthropized environments. Another finding was that the area was in secondary succession. The pioneer species presented the largest seeds and this characteristic is associated with the need for nutrient reserve that allows the embryo to germinate and last for a longer period without the need for exogenous nutrients, an essential condition for the Caatinga. With the advancement of ecological succession and the establishment of a more consolidated plant community, competition for resources, the frequent dispersion vector type and the nature of the environmental stresses present, the seeds may be smaller.